RETAINING MILLENNIALS ENGAGEMENT AND WELLBEING THROUGH CAREER PATH AND DEVELOPMENT - Sista Mayangdarastri; Khanifatul Khusna (Journal of Leadership in Organizations, 2020)
The topic of Millennials (1980-1995) in the workplace raises many business conversations and studies. These past few years, Millennials have filled up the workplace and surprisingly brought an interesting phenomenon. Millennials easily leave their jobs to find another in less than two years after starting the job. The goal of this paper is to examine this phenomenon by understanding the factors related to high millennials turnover. Some things that will be explained related to millennials are their employee commitment, wellbeing, and the function of career path and development in retaining millennials. The method of this writing is through journal reviews. In many studies, millennials are explained to be aware of their wellbeing and value work-life balance. They are eager to learn more and make changes when they could. Organizations that do not provide millennials with a place to grow and explore their capabilities to the fullest would not earn their loyalty. Clear career path and career development create the environment in which millennials feel appreciated, and it leads to employee satisfaction and a healthy workplace. When employees are satisfied, they will perform better to achieve the organization's goals and their own goals. Eventually, satisfied millennials will possess a higher commitment to the organization. It is crucial for an employer to understand millennials' characteristics and provides them with opportunities to grow because millennials' trust must be sought through processes where millennials are looked after.